Males and females differ in reported sexual functioning with escitalopram treatment for major depressive disorder: A CAN-BIND-1 study report. (May 2022) - Espinola, Caroline W; Khoo, Yuelee; Parmar, Roohie; Demchenko, Ilya; Frey, Benicio N; Milev, Roumen V; Ravindran, Arun V; Parikh, Sagar V; Ho, Keith; Rotzinger, Susan; Lou, Wendy; Lam, Raymond W; et al.
Background: Antidepressant use for major depressive disorder (MDD) is frequently associated with sexual dysfunction. Aims: Cross-sectional and longitudinal relationships between antidepressant treatment outcomes and sexual functioning (SF) were evaluated separately for males and females receiving escitalopram. We further assessed the association between pre- and posttreatment SF. Methods: In all, 208 of the 211 CAN-BIND-1 trial participants (77 males and 131 females) with MDD and detectable drug blood levels were eligible for the analyses. All received escitalopram (10–20 mg) for 8 weeks. At baseline and Week 8, participants completed the Montgomery–Åsberg Depression Rating Scale (MADRS) and the SexFx scale, which measures sexual satisfaction and SF frequency. Mixed-model repeated measures assessed baseline to Week 8 SF changes among participants with different response/remission statuses. Multiple linear regression analyses examined SF differences between treatment outcomes at Week 8 as well as associations between pretreatment and eventual SF. Results: For both sexes, overall sexual satisfaction improved among responders but not among nonresponders ( p < 0.05). For females, overall SF frequency did not change significantly over time regardless of response status. For males, overall SF decreased significantly among nonresponders; orgasm decreased significantly among nonresponders and, to a lesser extent, among responders ( p < 0.05). For both sexes, pretreatment SF was significantly associated with SF at Week 8 across all domains ( p < 0.05). Conclusion: For both sexes, sexual satisfaction improves with response to escitalopram. For females, the response does not correspond to improvements in SF frequency. For males, SF frequency, particularly that of orgasm, declines regardless of response/nonresponse. ClinicalTrials.gov identifier: NCT01655706